2012
DOI: 10.1007/978-1-61779-545-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hammerhead Ribozyme Reactions

Abstract: Hammerhead ribozymes are small catalytic RNA motifs ubiquitously present in a large variety of genomes. The reactions catalyzed by these motifs are both their self-scission and the reverse ligation reaction. Here, we describe methods for the generation of DNA templates for the subsequent in vitro transcription of hammerhead ribozymes. This is followed by a description of the preparation of suitable RNA molecules for both reaction types, and their kinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The difference between the resulting folding energies was then used to identify true positive HHR motifs among the primary hits. In vitro cleavage kinetics (Kalweit et al 2012) served to verify the chosen energy parameters on the example of newly identified motifs from Xenopus tropicalis (Seehafer et al 2011).…”
Section: Structure-based Search Approachesmentioning
confidence: 99%
“…The difference between the resulting folding energies was then used to identify true positive HHR motifs among the primary hits. In vitro cleavage kinetics (Kalweit et al 2012) served to verify the chosen energy parameters on the example of newly identified motifs from Xenopus tropicalis (Seehafer et al 2011).…”
Section: Structure-based Search Approachesmentioning
confidence: 99%
“…Templates for in vitro transcription were generated synthetically using partially overlapping primers in recursive PCR reactions, as described earlier (Kalweit et al 2012). The primers of these PCR reactions are listed in Supplemental Table S1 and add XhoI sites at the 5 ′ and 3 ′ ends of the fragment for subsequent cloning in expression vector pDneo2a lacZ (Wiegand and Hammann 2013).…”
Section: In Vitro Transcriptionmentioning
confidence: 99%
“…The self-cleavage reactions were analyzed as described previously (Kalweit et al 2012). Kinetic analyses were carried out for each variant at least in duplicate, and deviations in the determined kinetic parameters were below 20%.…”
Section: Kinetic Analysis Of the In Vitro Self-cleavage Reactionmentioning
confidence: 99%
See 1 more Smart Citation